Faktor-Faktor yang Berhubungan dengan Perilaku Kesehatan dan Keselamatan Kerja (K3) pada Petugas Cleaning Service di RSUD Ulin Banjarmasin - Dinda Puspitasari; Mahmudah Mahmudah; Hilda Irianty; Norfai Norfai (Universitas Baiturrahim, 2026)
Unsafe behavior is an action that can cause workers to have accidents or injuries, for example, ignoring the correct use of PPE, joking excessively when doing work, and wrong posture when working. At Ulin Banjarmasin Hospital, solid medical waste management is carried out by cleaning service officers who are the spearhead in waste management in hospitals. This study aims to determine the relationship between knowledge, attitudes, working periods, and K3 training with K3 behavior in cleaning service officers at Ulin Banjarmasin Hospital in 2024. This study was conducted using a quantitative method with a cross sectional research design. The research population is all cleaning service officers at Ulin Banjarmasin Hospital which totals 208. A sample was taken from 68 respondents using a proportional random sampling technique. Data collection using questionnaire sheets and data analysis using chi-square statistical test (α=0.05). Based on the results of the statistical test, there was a relationship between knowledge (p-value = 0.001) and attitude (p-value = 0.000) with K3 behavior in cleaning service officers at Ulin Banjarmasin Hospital in 2024. There was no relationship between working period (p-value = 0.567) and K3 training (p-value = 0.857) with K3 behavior in cleaning service officers at Ulin Banjarmasin Hospital in 2024. It is hoped that cleaning service officers can improve knowledge and attitudes so that they can meet K3 standards in carrying out medical waste management in hospitals